Multiple effects of Escherichia coli Nissle 1917 on growth, biofilm formation, and inflammation cytokines profile of Clostridium perfringens type A strain CP4. Issue 3 (11th March 2014) - Jiang, Yanlong; Kong, Qingke; Roland, Kenneth L.; Wolf, Amanda; Curtiss, Roy
Abstract Clostridium perfringens is an important Gram‐positive pathogen responsible for food poisoning, necrotic enteritis, gas gangrene, and even death. Escherichia coli Nissle 1917 (EcN) is a well‐characterized probiotic strain with demonstrated benefits. In this study, we evaluated the effects of EcN on growth, toxin production, biofilm formation, and inflammatory cytokine responses of C. perfringens. In vitro co‐culture experiments demonstrated that EcN inhibited growth, gas production, and toxin production (α‐toxin and NetB) of C. perfringens in a dose‐dependent manner. The growth inhibition effect was not observed when C. perfringens was incubated with EcN cell‐free supernatants (CFSE), suggesting that growth inhibition was caused by nutrition competition during co‐incubation. In vitro studies demonstrated that pre‐incubation with EcN did not inhibit C. perfringens attachment to Caco‐2 cells, but did reduce C. perfringens total number, toxin production, and cytotoxicity after 24 h. The similar growth inhibition results were also observed during the formation of C. perfringens biofilm. Finally, pre‐incubation of EcN with RAW264.7 cells significantly decreased the production of inflammatory cytokines caused by the introduction of C. perfringens. Our results indicate that EcN can inhibit many of the pathological effects of C. perfringens in vitro conditions.